RITUAL AS INDICATIVE OF A CODE OF VALUES IN HEMINGWAY'S IN OUR TIME - Stegh Carnati, Anna (Revista Letras, 1982)
This article discusses the concepts of ritual and code which Hemingway develops in his book In Oar Time, which comprises a series of short-stories, intimately connected to one another, which tell us in chronological order about the childhood and adolescence of Nick Adams, known as the "Hemingway hero". In this book, which can be considered as an initiation ritual, we can observe the process of apprenticeship of Nick Adams, who tries to elaborate a code of ethics, that will permit him to live adequately in a world of violence, disorder and misery. In order to achieve his aims, he tries to acquire certain principles of honour, courage and endurance, which will allow him to conduct himself well despite the adversities he may encounter in life. In the last story of the book, entitled Big Two-Hearted River, we can observe a series of rituals symbolic of code: the ritualistic codified actions provide adequate metaphors for the 'inner code' of the protagonist.